Clearing the air on surgical plume. Issue 1 (1st November 2021) - Watters, David A.; Foran, Paula; McKinley, Sharryn; Campbell, Graeme
Abstract: Background: Surgical smoke or plume is produced by a variety of surgical coagulators and dissectors. A number of jurisdictions have recently introduced policies to reduce the associated occupational health risks including WorkSafe Victoria and New South Wales Health. Method: This paper is a narrative review of potential risks, including any associated with COVID‐19, and options for mitigation. Results: Surgical smoke or plume contains potentially toxic chemicals, some of which are carcinogens. Plume may also contain live virus, notably Human Papilloma and Hepatitis B, though any possible viral transmission is limited to a few case reports. Despite identifying COVID‐19 ribonucleic acid fragments in various body tissues and fluids there are no current reports of COVID‐19 transmission. Although plume is rapidly removed from the atmosphere in modern operating rooms, it is still inhaled by the operative team. Mitigation should include ensuring diathermy devices have evacuators while plume extraction should be standard for laparoscopic procedures. Consideration needs to be given to the potential to compromise the operating field of view, or the noise of the extractor impairing communication. There is an increasing range of suitable products on the market. The future includes pendant systems built into the operating room. Conclusion: The potential risks associated with surgical plume cannot be ignored. Health services should invest in plume extraction devices with a view to protecting their staff. The conduct of the operation should not be compromised by the devices chosen. Future operating theatres need to be designed to minimize exposure to plume. Abstract : Surgical plume is a potential occupational health and safety issue for the operative team. It contains potentially hazardous chemicals and possibly may able to transmit viruses. Health services need to invest in smoke evacuation devices but these also require surgical team buy‐in to ensure smoke elimination measures are adopted in practice.